Fasetowany język: bilingwalna poezja Ireny Klepfisz w poetyckim dyskursie o Zagładzie - Kubińska, Olga (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The bilingual poetry of Irena Klepfisz, a Polish-born Jewish-American poet, seems to constitute a unique case of Holocaust poetry. The poet, an intellectual and activist engaged in lesbian, queer, feminist and gender movements, advocates the reading of Holocaust poetry within the ramifications of gender oriented cultural theories. Her bilingual poetry undermines the hypothesis of the postvernacularity of contemporary Yiddish. The paper substantiates the thesis that the choice of the target language in the translaton of bilingual Holocaust poetry has clear axiological underpinnings.